1996
DOI: 10.1152/ajpendo.1996.270.4.e552
|View full text |Cite
|
Sign up to set email alerts
|

Effects of growth hormone and IGF-I on glucocorticoid-induced protein catabolism in humans

Abstract: The effects of similar increases in total insulin-like growth factor I (IGF-I) plasma concentrations achieved by either recombinant human (rh) growth hormone (GH) or rhIGF-I administration on whole body protein and glucose kinetics were assessed. Twenty-six healthy subjects received methylprednisolone (0.5 mg.kg-1.day-1 orally) during 6 days in combination with either placebo (saline sc), GH (0.3 mg.kg-1.day-1 sc), or IGF-I (80 micrograms.kg-1.day-1 sc) in a double-blind randomized fashion. Glucocorticoid admi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
19
0
1

Year Published

1998
1998
2011
2011

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(22 citation statements)
references
References 4 publications
2
19
0
1
Order By: Relevance
“…The enhanced anti-catabolic outcome with early IGF-I treatment may also allow the use of lower doses of IGF-I, which could minimise the suppression of growth hormone and insulin secretion (e.g. Oehri et al 1996) and development of clinical side effects ( Jabri et al 1994, Thompson et al 1995. A recent report by Butterfield et al (1997) has shown that IGF treatment in old women had anabolic effects on whole body and muscle protein synthesis rates consistent with our observations in the old-rat model.…”
Section: Experimental Treatmentsupporting
confidence: 88%
“…The enhanced anti-catabolic outcome with early IGF-I treatment may also allow the use of lower doses of IGF-I, which could minimise the suppression of growth hormone and insulin secretion (e.g. Oehri et al 1996) and development of clinical side effects ( Jabri et al 1994, Thompson et al 1995. A recent report by Butterfield et al (1997) has shown that IGF treatment in old women had anabolic effects on whole body and muscle protein synthesis rates consistent with our observations in the old-rat model.…”
Section: Experimental Treatmentsupporting
confidence: 88%
“…IGF-1 is an anabolic peptide and promotes growth not only by increasing proliferation, cell survival, and protein synthesis but also by decreasing protein breakdown. 25,[41][42][43] In models of catabolism, such as fasting, 44 burn injury, 45 and glucocorticoid treatment, 26 IGF-1 treatment decreases mRNA abundance of components of the Ub-pathway and therefore the Ub-proteasome pathway is considered as a mediator of the anti-proteolytic actions of IGF-1. Furthermore, IGF-1 is known to down-regulate the expression of the ubiquitin ligases atrogin-1 and MuRF-1, both important in skeletal muscle for the targeting of proteins to be degraded through the Ub-pathway.…”
Section: Discussionmentioning
confidence: 99%
“…Urinary hydroxyproline was measured by a modified spectrophotometric assay (Woessner 1961, Podenphant et al 1984 and urinary pyridinoline and deoxypyridinoline by reverse-phase ion-paired HPLC (Seibel et al 1989, Black et al 1989. Serum total IGF-I and GH were measured as described previously (Oehri et al 1996).…”
Section: Methodsmentioning
confidence: 99%